Diversidade de bemisia tabaci na américa latina e detecção de seus endossimbiontes - Barbosa, Leonardo da Fonseca [UNESP] (2014)
The whitefly Bemisia tabaci (Gennadius) is a com plex of at least 36 cryptic species. It is one of the most important agricultural pests in the world, being vector of begomoviruses (genus Begomovirus , family Geminiviridae ) and crinivirus (genus Crinivirus , family Closteroviridae ) that cause serious probl ems in plants in many countries worldwide. Since the late 80s, the Middle East - Asia Minor 1 species – MEAM1 (known as biotype B) has emerged in many tropical and subtropical regions of the world, displacing native populations of B. tabaci . Previous work de monstrated that in Brazil at least two indigenous species called New World (NW, formerly the A biotype) and New World 2 (NW2) were still present in São Paulo State. Our first chapter entitled “Indigenous American species of the Bemisia tabaci complex are s till widespread in the Americas” highlight that MEAM1 has not completely displaced the native B. tabaci from the Americas. NW is present at least in Argentina, Brazil, Martinique, Mexico, United States and Venezuela, and NW2 in Argentina, Bolivia and Brazi l. Wild plants ( Euphorbia sp. and Ipomoea sp.) as well ...